Obtenção e caracterização de emulsão para correção de escoamento de óleo pesado - Silva, Wolney Lima (2010)
Extracting and producing heavy oil presents many difficulties, promoted by the nature of the constant quantities involved, such as viscosity of the oil, the means through where it moves the salinity of water, oil composition, the temperature and so forth. In the pumping, the amount of oil which is drawn is not enough to meet the expenses, that is, the cost-effectiveness has not been satisfactory. This work (Collection and Characterization of Emulsion to the correction of Heavy Oil Flow) sought to analyze the physical and chemical behavior and rheology of emulsions regarding the mobility and displacement of Heavy Oil. With the prior characterization of heavy oil from a study in the wells of the regions and UN-SEAL using sodium dodecyl sulfate (SDS) emulsion type water and oil were obtained (W / O). To the obtainment and the formulation of the oil-water emulsion type, the use of surfactant was essential to the choice of the anionic SDS, since this surfactant is widely used in the petroleum industry. The developments made in this work, in other words, obtaining the w / o emulsions, showed a decrease in viscosity, the shear stress with increasing shear rate with the behavior of a pseudo plastic fluid. It follows that achieving the w / o emulsions, in the micellar concentrations such as 6.67 x 10-2 g.mL-1, 1.0 x 10-1 g.mL-1 and 3.75 g.mL-1 to obtain the w / o emulsions were satisfactory, compared to concentrations of ions present in the oil sample, the pH, the levels of aromatics, resins and asphaltenes, the API gravity, the density, the shaking time, 6 min , the rotation speed of 1000 RPM ± 50, the temperature of 27 ° C, with the breaking time o the emulsion 300 min observed that the viscosity of emulsified oil, tension and shear rate were reduced. Therefore, emulsion water / oil (W / O), obtained in this study achieved the goal of working to reduce the parameters that affect the mobility of heavy oil.